Prediction of histological grade of endometrial cancer by means of MRI. Issue 103 (June 2018) - Bonatti, Matteo; Pedrinolla, Beatrice; Cybulski, Adam Jerzy; Lombardo, Fabio; Negri, Giovanni; Messini, Sergio; Tagliaferri, Tiziana; Manfredi, Riccardo; Bonatti, Giampietro
Highlights: Pre-operative biopsy under-grades endometrial cancer in 18.9% of the cases. Deep myometrial infiltration is significantly associated with high grade endometrial cancer. Neoplasm/uterus volume ratio is significantly higher in high grade endometrial cancer. ADC histogram analysis does not allow to identify high grade endometrial cancer. Abstract: Objectives: To evaluate the ability of MRI in predicting histological grade of endometrial cancer (EC). Methods: IRB-approved retrospective study; requirement for informed consent was waived. 90 patients with histologically proven EC who underwent preoperative MRI and surgery at our Institution between Sept2011 and Nov2016 were included. Myometrial invasion (</>50%) was assessed. Neoplasm and uterus volumes were estimated according to the ellipsoid formula; neoplasm/uterus volume ratio (N/U) was calculated. ADC maps were generated and histogram analysis was performed using commercially available software. MRI parameters were compared with the definitive histological grade (G1 = 28 patients, G2 = 29, G3 = 33) using ANOVA and Tukey-Kramer tests. Results: Deep myometrial invasion was significantly more frequent in G2-G3 lesions than in G1 ones (p < 0, 005). N/U ratio was significantly higher for high-grade neoplasms (mean 0, 08 for G1, 0, 16 for G2 and 0, 21 in G3; P = 0, 002 for G1 vs. G2-G3); a cut off value of 0, 13 enabled to distinguish G1 from G2-G3 lesions with 50% sensibility and 89% specificity. ADC values didn't show any statistically significant correlation with tumour grade. Conclusions: N/U ratio >0.13 and deep myometrial invasion are significantly correlated with high grade EC, whereas ADC values are not useful for predicting EC grade.